Detection of Dengue Virus-Specific IgM and IgG Antibodies through Peptide Sequences of Envelope and NS1 Proteins for Serological Identification - Pradeep Kumar Nagar; Deepali Savargaonkar; Anupkumar R. Anvikar (Journal of Immunology Research)
Dengue is an acute febrile illness caused by positive-sense single-stranded RNA virus, belonging to the family Flaviviridae and genus Flavivirus. Transmission of virus among the individuals occurred by blood-feeding Aedes mosquitoes. This virus has four serotypes differentiated on the basis of antibody neutralization assay. At present, there is no particular treatment or vaccine candidate available for dengue infection. Approximately 3.9 billion human populations are at risk of dengue virus (DENV) infection. Thus, precise diagnosis of dengue at the early stage is very essential for disease control and effective therapy in order to treat or prevent severe complications. Indeed, the accurate diagnosis of DENV remains a problem because of low detection accuracy along with high testing price. Sensitivity and specificity of available kits vary from test to test, and cross-reactivity with other Flavivirus is a challenging issue for diagnosis. In this study, linear epitopes of envelope (E) and NS1 proteins were identified to diagnose the DENV. Whole protein sequences of E and NS1 of DENV were obtained from UniProtKB database. On the basis of algorithm prediction from DNASTAR, BCEPRED, and IEDB data resources, twelve peptides of E (EP1 to EP12) and eight peptides of NS1 (NS1-1 to NS1-8) were selected, which were common in all serotypes. Sequence homologies of peptides with other Flavivirus were checked by Multiple Sequence Alignment Tool ClustalX2. Peptide sequences were synthesized chemically by solid-phase peptide synthesis technique. Dengue-specific IgM and IgG (secondary response) antibodies in the patient’s antisera were tested with the peptides using ELISA protocol. Peptides EP1, EP2, EP4, EP7, EP10, and EP12 of E protein and NS1-1, NS1-3, NS1-4, NS1-7, and NS1-8 of NS1 protein were considered the best immunoreactive peptides with the sensitivity (73.33-96.66%) and specificity (82.14-100%). Such peptides together can be used to construct the multiple antigen peptides (MAP) or multiplexed microbeads for designing a precise, cost-effective, and easy-to-make peptide-based immunodiagnostic kit for DENV detection.